STABILITAS FISIK FORMULA OPTIMUM GEL EKSTRAK ETANOLIK KULIT PISANG AMBON (Musa paradisiaca L.) DENGAN KOMBINASI BASIS KARBOPOL DAN CMC-NA MENGGUNAKAN METODE SLD (Simplex Lattice Design) - , NADYA AGUSTINA; , Dr. Mimiek Murrukmihadi, SU., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ethanolic extract of unripe banana peel (Musa paradisiaca L.) has been proved to accelerate wound healing. Formulations in gel dosage forms considered suitable for treatment of injuries. The combination of carbopol and CMC-Na as the bases is expected to improve physical properties compared to the use of a separate base. This study aims to determine the physical stability of the gel with the optimum formula with combination of carbopol and CMC-Na. The study was conducted with a banana peel maceration with 70% ethanol to obtain a thick extract with a concentration of 10%. Formula used for optimization with a combination of two variations bases, carbopol and CMC-Na, ie Formula A (2:3%), Formula B (0.5: 4.5%), and formula C (1,25:3,75%). The data obtained from testing the physical properties of tablets prepared with the program Design Expert Â® Simplex Lattice Design program t o obtain optimum formula. Physical stability of the optimum formula then verified and tested for 4 weeks then analyzed statistically using one-way Annova. The results obtained showed that the combination of the two bases that produce optimum physical properties requires a combination of 1,1 % carbopol and 3,9 % CMC-Na. The verification results show that the equations obtained from the Design Expert can be used for the viscosity and dispersive power parameters. The optimum formula of gel physically stable for 4 weeks of storage.